Perbandingan Kualitas Kompos Limbah Tandan Kosong Kelapa Sawit Dengan Berbagai Perlakuan Bioaktivator: Perbandingan Kualitas Kompos Limbah Tandan Kosong Kelapa Sawit Dengan Berbagai Perlakuan Bioaktivator - Dai Maulana; Fitria Nugraheni Sukmawati; Hartini; Syamsudin Harahap (JURNAL ILMIAH AGRINECA, 2026)
Empty fruit bunches of oil palm (EFB) are solid waste generated from the palm oil industry. One alternative utilization of EFB is as raw material for compost production. This study aimed to determine the effect of local microorganism bioactivators on the quality of EFB compost. The research was conducted at the greenhouse of the experimental garden of Politeknik LPP Yogyakarta, Wedomartani, Sleman. The study used a non-factorial Completely Randomized Design (CRD) with four bioactivator treatments, namely EM4, bamboo shoot MOL, shallot MOL, and POME MOL. he observed parameters included the physical properties of compost (temperature, color, odor, moisture content, and pH), the chemical properties of compost (organic C content, C/N ratio, and total N, P, and K), as well as compost quality assessed through a rice seed germination test, which was analyzed descriptively. The results showed that chemically, the C-organic content of all treatments met the minimum standard; however, the C/N ratio was still above the compost maturity standard. The POME MOL treatment produced the highest N and P contents and the lowest C/N ratio, while the highest germination percentage was obtained from the EM4 treatment at 84%. Based on these results, POME MOL was the best local microorganism bioactivator for producing EFB compost with quality close to the standard and without inhibiting plant growth.